Representations of Swedish rural areas in the last 50 years (Sociologisk Forskning, 2025)
This article focuses on something that is often taken for granted in rural sociology, namely the dichotomous image of rural areas as either idyllic and innovative or abandoned and backwards. It is common for both critical researchers and rural advocates to try to challenge reductive representations with questions about what it really is like, but there is a lack of longitudinal studies that analyze how the image of rural areas has emerged and changed over time, for example in political discourses. This historical perspective is necessary to understand contemporary representations of rural areas and their underlying assumptions. This study provides such an overview by analyzing ten government investigations from the last 50 years using Carol Bacchi’s "what is the problem represented to be" approach. I identify problems that have existed for a long time and things that are new or only existed for a short time. Among other contributions, the article shows how the growth paradigm has become a taken for granted starting point for how rural areas are represented in the political discourse.
Keywords: Rural; Rurality; Representation; Discourse; Sweden; Growth